The effect of phytoadditive combinations on growth and consumption indices and resistance to Aeromonas hydrophila in common carp (Cyprinus carpio) juveniles - Erol-Florian Gabor; Aurel Şara; Mihai Benţea; Cǎlina Creţa; Anca Baciu (Scientific Papers Animal Science and Biotechnologies, 2023)
The present trial aimed to determine the effects of some phytoadditive combinations (garlic + ginger – group 1E and oregano + Echinacea – group 2E) on the growth and consumption indices and resistance to Aeromonas hydrophila in common carp (Cyprinus carpio) juveniles reared in a recirculating system. Dietary administration of phytoadditives led to a higher body weight gain in the experimental groups compared to the control, also leading to a higher specific growth rate and to a lower FCR value. Also the survival rate was improved by the dietary treatment with the phytoadditive combination, the highest survival rate being recorded in the 1E group. A test infection was carried out after 13 weeks of feeding, in order to determine the effect of the phytoadditive combinations on disease resistance. So, the survival rate was improved in all the experimental groups compared to the control. Selenium content of meat was also determined, the highest values being recorded in group 1E, both the experimental groups presenting higher values than the control group. Dietary treatment using phytoadditive combinations had a positive influence on the growth and consumption indices, also improving the survival rate and disease resistance